PENERAPAN PEMBIAYAAN MURABAHAH DI KSPPS USAHA MULYA MASJID RAYA PONDOK INDAH JAKARTA - Alaik Rifqi Sidqon; Jaharuddin Jaharuddin (Media Riset Bisnis Ekonomi Sains dan Terapan, 2023)
The main objective of this research is to assess the extent to which the implementation of murabahah financing aligns with the established Sharia principles. Furthermore, this study aims to analyze the procedures and margin calculations used in applying for murabahah financing at the Sharia Financing Savings and Loan Cooperative (KSPPS) of Usaha Mulya Masjid Pondok Indah. The method employed in this research is descriptive qualitative. In addressing this issue, data collection is carried out through direct field observation, interviews, and documentation gathering. The research findings indicate that Usaha Mulya Masjid Pondok Indah's KSPPS utilizes the products of Murabahah, Ijarah, and Hiwalah to empower the community's economy through Sharia-compliant products. The murabahah financing procedure involves purchasing goods at a specific price, verifying customer applications, conducting surveys, committee assessments, reselling with a profit margin, and notarized contract signing. The profit-sharing margin per month at Usaha Mulya Masjid's KSPPS is 1%, whereas it is 3% at conventional KAWI Honda, illustrating the equitable approach of Sharia financial institutions. The implementation of the murabahah contract at Usaha Mulya Masjid's KSPPS in Pondok Indah, Jakarta aligns with Sharia principles, based on the nine fundamental implementation principles from the Fatwa of the Indonesian Council of Ulama (DSN MUI) No: 04/DSNMUI/IV/2000.